2018
DOI: 10.3390/su10103388
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Tourists’ Sociodemographic Characteristics on the Travel Motivation and Satisfaction: The Case of Protected Areas in South China

Abstract: Western studies on nature-based tourism have long explored the relationships among tourists’ sociodemographic characteristics, motivation and satisfaction as a way of predicting their visitation patterns and travel behaviours. Relatively few studies have been conducted in the Chinese context given its varied and extensive landscapes. This paper seeks to fill this gap using data from questionnaire surveys conducted in two popular and prestigious forest nature reserves in Guangdong province between August and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 70 publications
8
56
2
3
Order By: Relevance
“…Results of this study are in accordance with previous research (Haukeland et al, 2010;Jensen, 2011;Kim et al, 2003), which also indicates that sociodemographic characteristics have an influence on motives for visit. Our study partially confirmed findings obtained by Ma et al (2018), which admittedly used other variables but came to conclusion that sociodemographic characteristics have significant impact on motivation for visiting national parks.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Results of this study are in accordance with previous research (Haukeland et al, 2010;Jensen, 2011;Kim et al, 2003), which also indicates that sociodemographic characteristics have an influence on motives for visit. Our study partially confirmed findings obtained by Ma et al (2018), which admittedly used other variables but came to conclusion that sociodemographic characteristics have significant impact on motivation for visiting national parks.…”
Section: Resultssupporting
confidence: 90%
“…Their study identified four push factors for visiting national parks, such as recreation and knowledge seeking, appreciating wildlife and feeling close to nature and six pull factors such as abundance of wildlife, availability of different animal species, availability of different plant species, wilderness, beautiful landscape and peaceful/quiet experiences. Ma, Chow, Cheung, Lee, and Liu (2018) used sociodemographic characteristics, motivation and satisfaction to predict visitation patterns and travel behaviors. Their findings showed that education level is negatively correlated with tourist' satisfaction as well as a motivation regarding social influence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results show that there was no outlier, indicating that the data were distributed normally. In order to avoid common method bias, we tested several methods including Harman's single factor test, partial correlation method, and the multi-trait-multimethod model [113,114]. All the results showed that there was no common method bias in the data, meaning the data were suitable for further analysis.…”
Section: Analysis Of Normality and Common Methods Biasmentioning
confidence: 99%
“…In this sense, Nickerson et al (2016) concluded that sustainable tourists are willing to spend more, which can increase the benefit of offering sustainable tourism destinations. On the other hand, Ma et al (2018) conducted a study in the Nanling National Forest Park and the Dinghushan National Nature Reserve, finding that the most important factor in Chinese tourists is "relaxation and nature exploration". In contrast, Chow et al (2019) conducted a study to visitors to the Ramsar wetland in Hong Kong, finding that the most important motivations were relaxation, escape from daily life, and physical and mental health.…”
Section: Theoretical Framework Motivations In Ecotourismmentioning
confidence: 99%